Optimization of the differential pulse anodic stripping voltammetry technique for determination of cadmium in Pengkalan Chepa River, Kelantan - Zulkiply, Nor Amalina (Universiti Sains Malaysia, 2009)
Cadmium is one of heavy metal that can cause river water pollution by waste from factories. Common exposure of human or animal towards cadmium will cause toxicity. In determination of cadmium, voltammetric technique was used since it is highly sensitive, low cost and low limit of detection. This technique was used for qualitative and quantitative determination of cadmium in water samples. Samples were collected from five rivers; Sungai Alor B, Sungai Alor Lintah, Sungai Keladi, Sungai Pengkalan Chepa and Sungai Pengkalan Chepa 2 which are tributaries of main river, Pengkalan Chepa River at different depth (surface and bottom). Differential Pulse Anodic Stripping Voltammetry (DPSA V) technique was carried out using three electrodes, hanging mercury drop electrode (HMDE) act as working electrode, Ag/AgCI/KCI saturated act as reference electrode and platinum electrode act as auxiliary electrode. The supporting electrolyte used was acetate buffer (1.38 M, pH 4.6). The optimum voltammetric parameters to determine cadmium in river water were initial potential (Ei) -1 V, final potential (Er) -0.2 V, scan rate (v) 5 mV/s, voltage step 0.005 V, voltage step time 1 s, deposition potential (Eacc) -1 V, deposition time (tacc) 60s and equilibrium time (teq) 1000 s. Using this optimized parameters, peak potential (Ep) for cadmium standard was found at -0.632 V. The linear range of cadmium was observed over the concentration range 0.26 ppm to 1.32 ppm with correlation coefficient (r) 0.993, standard deviation (SD) 0.500, sensitivity 10.227 nA/ppm and limit of detection 147 ppb. The method had been successfully applied for determination of cadmium in real samples. The results showed that cadmium was absent in all the samples.